2001
DOI: 10.1038/sj.cdd.4400876
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine inhibits phosphorylation of translational regulators linked to mTOR

Abstract: Treatment of Swiss 3T3 cells with staurosporine resulted in dephosphorylation of two proteins which play key roles in regulating mRNA translation. This occurred before the execution of apoptosis, assessed by caspase-3 activity. These translation regulators are p70 S6 kinase, which phosphorylates ribosomal protein S6, and eukaryotic initiation factor (eIF) 4E binding protein 1 (4E-BP1), which both lie downstream of the mammalian target of rapamycin (mTOR). This resulted in decreased p70 S6 kinase activity, deph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
(38 reference statements)
2
31
0
Order By: Relevance
“…However, it did not restore the fluorochrome export in UVB-irradiated cells (Figure 2b). Conversely, staurosporine, [19][20][21] that induced efficient and early lymphocyte death via apoptosis (Figure 2a) did even increase the fluorochrome export (Figure 2c), indicating that apoptosis per se does not downregulate the activity of ABC transporters.…”
Section: Uvb-induced Inhibition Of Abc Transporters Does Not Correlatmentioning
confidence: 94%
“…However, it did not restore the fluorochrome export in UVB-irradiated cells (Figure 2b). Conversely, staurosporine, [19][20][21] that induced efficient and early lymphocyte death via apoptosis (Figure 2a) did even increase the fluorochrome export (Figure 2c), indicating that apoptosis per se does not downregulate the activity of ABC transporters.…”
Section: Uvb-induced Inhibition Of Abc Transporters Does Not Correlatmentioning
confidence: 94%
“…Several previous studies have shown that during the early phase of the cellular response to inducers of apoptosis, the extent of phosphorylation of 4E-BP1 decreases, 83,101,124,125 and that the hypophosphorylated 4E-BP1 thus generated binds to eIF4E in competition with eIF4GI or II. This decreases the availability of the eIF4F complex for initiation of translation.…”
Section: Effects Of Modifications Of 4e-bp1mentioning
confidence: 99%
“…Both dephosphorylation and caspase-mediated cleavage of 4E-BP1 have been shown to occur in cells exposed to staurosporine and the DNA-damaging agent etoposide. [124][125][126] Cleavage occurs at Asp-24, close to the N-terminus of the protein (Figure 3). The activation of p53 also results in the cleavage of 4E-BP1, but in this case, the cleavage is a z-VAD.FMK-insensitive event, suggesting that it is mediated by another type of protease (C Constantinou and MJ Clemens, unpublished data).…”
Section: E-bp1mentioning
confidence: 99%
“…The resulting major fragment of 4E-BP1 is indicated as 'D4E-BP1' apoptosis, also led to inhibition of mTOR signaling. 60 Since mTOR signaling positively regulates cell growth and proliferation, and ribosome biogenesis, this shut-down of mTOR signaling may represent a response of cells to adverse conditions that may ultimately compromise cell survival. By affecting both cap-dependent and -independent translation, it may also alter the balance of protein expression and thereby modulate the events that trigger commitment to apoptosis, an issue that is dealt with in more detail below.…”
Section: Regulation Of Eif4e During Apoptosismentioning
confidence: 99%